2009
DOI: 10.1111/j.1365-2230.2008.03104.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression and localization of vascular endothelial growth factor and vascular endothelial growth factor receptor-2 in human epidermal appendages: a comparison study by immunofluorescence

Abstract: A potential VEGF/VEGFR-2 autocrine pathway may be defined by the coexpression of VEGF and VEGFR-2 in human skin epidermal appendages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
46
0
5

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 17 publications
1
46
0
5
Order By: Relevance
“…It is well documented that platelet rich plasma preparations (PRP) ignites hair cycle and hair canal formation by secreting various proteins like platelet derived growth factor and cytokines as well as through enhancing cells proliferation. Anti-apoptice effects of PRP also increase survival and anagen phase of hair cycle [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…It is well documented that platelet rich plasma preparations (PRP) ignites hair cycle and hair canal formation by secreting various proteins like platelet derived growth factor and cytokines as well as through enhancing cells proliferation. Anti-apoptice effects of PRP also increase survival and anagen phase of hair cycle [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…VEGF mRNA expression in normal human hair follicles varies during the hair cycle. It is strongly expressed in the anagen phase and decreased in the catagen and telogen phases (28,29). Our experimental results, therefore, suggest that treatment of DP cells with adenosine is effective in maintaining high IGF-1 and VEGF expressions and the ability to induce hair growth in DP cells.…”
Section: Discussionmentioning
confidence: 59%
“…The immunoreactivity analysis for VEGF showed that it was expressed in the hair bulb of primary and secondary hair follicles, the ORS, IRS, sebaceous glands (ductal and secretory portions), eccrine sweat glands (ductal and secretory portions), and epidermis. Man et al (2009) also showed that VEGF was expressed in anagen hair follicles, including the inner or outer root sheath, fiber root sheath, dermal papillae, and progenitors of the hair shaft and pluripotential epidermal matrix cells. Furthermore, VEGF expression and the MVD increased during the anagen to catagen transition in the primary and secondary hair follicles, and the change in MVD and VEGF expression in the dermis showed bimodal patterns, in which two peaks were observed in May and August.…”
Section: Relationship Between Vegf and Mvd Expressionmentioning
confidence: 99%
“…In particular, VEGF plays important roles in promoting angiogenesis by stimulating capillary proliferation, migration, and permeability, as well as tissue development, by regulating growth and differentiation (Ferrara et al, 2003;Tammela et al, 2005). VEGF expression has been observed in normal epidermis (Ballaun et al, 1995;Weninger et al, 1996), skin tumors (Weninger et al, 1996;Viac et al, 1997), hair follicles (Man et al, 2009), and sebaceous glands (Lachgar et al, 1996a,b;Kozlowska et al, 1998b). The latter two, together with eccrine sweat glands, are termed the 'epidermal appendages', and are lined with epithelial cells (Man et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation